Effects of Ethanol and Aqueous Terminalia chebula, Cyperus rotundus, Tinospora crispa and The Combined Remedy on Anti-Oxidant Activities and Capacities - Boonyuenyong, Kunsurapa; Chaiyawatthanananthn, Pannawat; Intarawan, Thanaporn; Houngiam, Katanchalee; Ngankogsoong, Yupa (Asian Medical Journal and Alternative Medicine, 2023)
Introduction: Plant antioxidants have an important role in the prevention of many degenerative diseases. A Thai herbal remedy in Worayokasarn scripture consists of three plants i.e., Terminalia chebula fruits (TC), Cyperus rotundus rhizomes (CR) and Tinospora crispa vines (TCL). In the previous studies, polyphenolic TC, methanol CR and ethanolic TCL extracts had free radical scavenging activity. These results support the use of the remedy and the herbal compounds for reducing free radicals. Objectives: To investigate ethanolic and aqueous extracts of the remedy and its plant ingredients on anti-oxidant activities and capacities. Methods: The remedy (RM) was macerated with 95% ethanol (RME) or water decoction (RMW). Dry TC, CR and TCL plants were extracted with ethanol maceration (TCE, CRE and TCLE, respectively) or water decoction (TCW, CRW and TCLW, respectively). All extracts were measured anti-oxidant activities by DPPH, FRAP and ABTS radical assays, and anti-oxidant capacities by measuring total phenolic content (TPC) and total flavonoid content (TFC). Results: RME and RMW had the anti-oxidant activities by DPPH method (EC50 = 11.00 and 53.49 µg/mL, respectively), ABTS assay (EC50 = 41.66 and 34.06 µg/mL, respectively) and FRAP values (220.78 and 228.84 mg Fe2+/g of extract, respectively), and had anti-oxidant capacities by TPC (48.16 and 64.95 mg GAE/g of extract, respectively) and TFC (116.56 and 134.06 mg QE/g of extract, respectively). Moreover, TCW showed very strong DPPH (9.43 µg/mL) and ABTS (11.40 µg/mL) activities and the highest TPC (142.15 mg GAE/g of extract). TCE and CRE had the highest FRAP value (467.14 mg Fe2+/g of extract) and TFC (182.30 mg QE/g of extract), respectively. Conclusions: The remedy and the three herbal extracts had antioxidant activities and capacities. The results supported that the remedy should be selected to use for reducing and preventing oxidation.